Vihtr'iitshik: A Stone Quarry Reported by Alexander Mackenzie on the Lower Mackenzie River in 1789 - Pilon, Jean-Luc (ARCTIC, 1990)
The analysis of archaeological specimens gathered in 1988 at the mouth of the Thunder River (MiTi-1), lower Mackenzie Valley, indicates that the locality's primary function was as a quarry/workshop. Historical and toponymic data show that this was likely the quarry identified by Alexander Mackenzie on 24 July 1789. Collections from the southwest Anderson Plain contain high proportions of Thunder River siliceous argillite, some obtained from beach gravels or till deposits, while some were obtained from primary geological deposits. In collections from peripheral areas, Thunder River siliceous argillite is occasionally found and often consists of the end-products of lithic reduction. It is especially interesting to confirm the presence of Thunder River siliceous argillite in Mackenzie Delta Inuit sites. A critical evaluation of all available data shows that Alexander Mackenzie's journal was relatively accurate with respect to this lithic source.